IMPLEMENTASI PERATURAN PRESIDEN NOMOR 70 TAHUN 2012 TENTANG PENGADAAN BARANG / LAYANAN OLEH UNIT ELEKTRONIK (E-PENGADAAN) PADA LAYANAN PENGADAAN (ULP) UNIVERSITAS LAMPUNG - Ngadiman Ngadiman (Wacana Publik, 2018)
This study aims to see the implementation of policies and constraints on communication process, resources, disposition and bureaucratic structure in the implementation of the procurement of goods/services based on electronic (eprocurement). This research used descriptive method with qualitative approach. Data was collected through in-depth interview study, documentation and observation, while the technique of the validity of data was done through triangulation, including triangulation methods, data sources and the data itself.The results of this study showed that e-procurement have demonstrated their success, although it hasn't been optimal, which gained efficiency and effectiveness on a number of indicators. From the aspect of time, the procurement process with e-procurement system proved faster because it only takes 14-18 working days, the conventional system takes more than 30 days' work through e-procurement can reduce the potential for corrupt practices, for a meeting between the auction committee and the auction participants islimited a lot. At the time of the auction is still widely practiced in the conventional direct meetings between the auction partipants and the auction committee which has opened the chance of occuring "negative transactions". With the e-procurement system of bid documents submitted in the form of soft through the internet and can only be opened as scheduled. The limiting factor of e-procurement in terms of planning activities and budget planof PSU ìsn't Uxcluded by the planning department, the emergence of a sense of dissatisfaction of staff employees PSU due to not match the workload carried by the additional amount of income earned, inaccuracy in transferring staff employees of PSU. The learnings we can get from this stuis that there was a strong commitment from top leadership level to their staff level as the executors in the real activities which is the essential factor of the key of the success of the e-procurement implementationsystem in University of Lampung.